Leadership style of Malaysian super six school rugby coaches / Idris Yusoff - Yusoff, Idris (Faculty of Sport Science and Recreation, 2017)
The purpose of this study was to identify Leadership Style of Malaysian Super Six School Rugby Coaches. A total of one hundred fifty (N=150) were selected via control sampling participated in this study. The instruments of this study were using demographic questionnaire and Leadership Sport Scale. Based on the descriptive analysis result, the coaching style used by the coaches was democratic style than autocratic style. Based on result of coaching behavior, athletes chose their coaches used often and occasionally for training behavior, social support and rewarding behavior. Based on the Pearson correlation result, there was no linear correlation between leadership style and school performances. Correlations of Autocratic Style showed the significant two tailed was 0.805, and Correlations of Democratic Style was 0.838.